2020
DOI: 10.25259/sni_38_2020
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunt complications in an adult population: A comparison of various shunt designs to prevent overdrainage

Abstract: Background: Overdrainage after cerebrospinal fluid diversion remains a significant morbidity. The hydrostatic, gravitational force in the upright position can aggravate this. Siphon control (SC) mechanisms, as well as programmable and flow regulating devices, were developed to counteract this. However, limited studies have evaluated their safety and efficacy. In this study, direct comparisons of the complication rates between siphon control (SC) and non-SC (NSC), fixed versus programmable, and flow- versus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…In fact, non-programmable GV may not be advisable when the required opening pressure is difficult to estimate before surgery [105]. It should be taken into account that some patients with lower intracranial pressures may benefit from non-siphon control valves [112]. GV may cause under-drainage in bedridden patients [113].…”
Section: Management Strategies In Shunt Overdrainagementioning
confidence: 99%
“…In fact, non-programmable GV may not be advisable when the required opening pressure is difficult to estimate before surgery [105]. It should be taken into account that some patients with lower intracranial pressures may benefit from non-siphon control valves [112]. GV may cause under-drainage in bedridden patients [113].…”
Section: Management Strategies In Shunt Overdrainagementioning
confidence: 99%
“…Desai et al [ 5 ] conducted a retrospective study involving 476 patients with a ventriculoperitoneal shunt in a single institution for five years duration. The study revealed that the overall complication rate of the shunt was 19%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent time, various ventriculoperitoneal shunts were designed to prevent overdrainage. [ 26 ] Further studies are needed to determine which shunt is the most appropriate for LOVA. We believe that patients with LOVA can benefit more from VP shunt surgery.…”
Section: Discussionmentioning
confidence: 99%